The impact of skim bantuan rumah Lembaga Zakat Negeri Kedah to asnaf in Kubang Pasu - Nur Fatin Husna, Mohd Nasir (2021)
This research aimed to study the impact of Skim Bantuan Rumah Lembaga Zakat Negeri Kedah (LZNK) to asnaf in Kubang Pasu. Based on two main objectives, this research focus of several main things which is the knowledge of Skim Bantuan Rumah Individu LZNK among asnaf in Kubang Pasu and the impact of Skim Bantuan Rumah Individu LZNK to asnaf in Kubang Pasu. For the first objective, this research explores the the knowledge of channel of information’s, types of Bantuan Rumah Individu LZNK and the procedure to get and submit application form among asnaf in Kubang Pasu. Secondly, this research studies the impact of Skim Bantuan Rumah Individu LZNK to asnaf in Kubang Pasu based on asnaf and zakat officer perspective. Hence, to make sure all objectives that have been listed are answered progressively, the most suitable method that can used is qualitative research methodology. This research integrated the source of relevant literatures and interviews. At the end of this paper, the researcher found the knowledge of Skim Bantuan Rumah Individu LZNK among asnaf in Kubang Pasu base on channel of information, types of Skim Bantuan Rumah Individu and procedure to get and submit application form. Besides that, the researcher also found the impact of Skim Bantuan Rumah LZNK in asnaf quality of life cover emotions, education, safe and comfortable and social problem. In addition, the researcher also suggests several improvements to the LZNK in order to increase the impact of Skim Bantuan Rumah LZNK to asnaf in Kedah. In conclusions, the impact of Skim Bantuan Rumah Individu needs to be further studied from a multidimensional perspective to ensure the impact of the Skim Bantuan Rumah Individu achieved in improve asnaf life.